Relationship between paternal psychological distress and involvement in childcare among fathers of preschool-aged children: mediating effect of maternal psychological distress - Hyeon Sik Chu; Hanyi Lee (BMC, 2019)
Abstract Background The role of the father as a co-caregiver is becoming increasingly important across cultures. Parental psychological distress is an influencing factor of maladaptive parenting behaviors and negative psychosocial outcomes in children. Considerable research has focused on psychological distress in parents, commonly experienced during the childrearing years; however, the relationship between paternal psychological distress and fathers' involvement in childcare has been less studied. This study aimed to examine this relationship. Methods This study explored the relationship between parental psychological distress and fathers' involvement in childcare by analyzing data from 1541 children and their parents from the 2011 Panel Study on Korean Children. Psychological distress was assessed using the Kessler 6-Item Psychological Distress Scale. Fathers' involvement in childcare was measured in terms of the quality and quantity of involvement, using a Father's Childcare Involvement Scale completed by mothers and the daily hours spent by fathers in childcare. Results The mean scores for paternal and maternal psychological distress were 5.26 ± 4.20 and 5.79 ± 4.42, respectively; for the quality of fathers' involvement in childcare, 14.46 ± 2.63; and for the quantity of fathers' involvement, 2.53 ± 1.62. Paternal psychological distress was significantly correlated with maternal psychological distress and fathers' involvement in childcare. Maternal psychological distress demonstrated a partial mediating effect on the relationship between paternal psychological distress and the quality of fathers' involvement in childcare for preschool-aged children (β = −.085, p < .001); this effect was significant (Sobel test; Z = 3.13, p = .002). Further, maternal psychological distress demonstrated a complete mediating effect on the relationship between paternal psychological distress and the quantity of fathers' involvement in childcare (β = −.065, p = .018); this effect too was significant (Sobel test; Z = 2.38, p = .018). Conclusions Paternal psychological distress influenced the quality and quantity of fathers' involvement in childcare and was mediated by maternal psychological distress. To promote fathers' involvement in childcare, a family-centered approach for childcare should reflect the triadic interaction of father-mother-child. These findings have implications for primary health professionals, as well as policymakers who design community health programs for early childhood.